2020
DOI: 10.18805/ajdfr.dr-1498
|View full text |Cite
|
Sign up to set email alerts
|

Study on Physico-Chemical and Microbial Quality of Raw Milk Collected From Different Places of Assi Region in Varanasi City, Varanasi

Abstract: The present study was conducted to evaluate the physico-chemical characteristics including Adulteration and Microbiological quality of cow raw milk collected from four different places of ASSI region in Varanasi. Samples were analysed to know the chemical composition, the results showed that the statistically average percentage of Moisture (87.46), Fat (3.87), Protein (3.15), Lactose (4.42), Ash (.712), pH (6.43) and acidity (0.147). The keeping quality of milk was evaluated by Methylene Blue Reduction Test (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(11 reference statements)
5
2
0
Order By: Relevance
“…The results of the biochemical tests done with each of the isolate are shown in Table 5. These result are in conformity with other South Asian studies such as Surve et al (2011), Dewangan et al (2017) and Gupta et al (2020). E. coli is an indicator organism to show if any sample/ objects is contaminated with materials of fecal origins.…”
Section: Proportion Of Milk Samples Positive With E Colisupporting
confidence: 92%
“…The results of the biochemical tests done with each of the isolate are shown in Table 5. These result are in conformity with other South Asian studies such as Surve et al (2011), Dewangan et al (2017) and Gupta et al (2020). E. coli is an indicator organism to show if any sample/ objects is contaminated with materials of fecal origins.…”
Section: Proportion Of Milk Samples Positive With E Colisupporting
confidence: 92%
“…1), which indicates that raw milk was free from different mixed adulteration and hazardous chemicals adulterant contents. In our present study findings, results also agreed with other researchers (Pandey et al 2019;Gupta et al 2020 andKarmaker et al 2020).…”
supporting
confidence: 94%
“…During the experimental period, raw milk MBRT (in hours) quality significantly retained maximum-minimum period (4.15±0.064 to 3.80±0.040 hrs) to change raw milk samples dye color from blue to white which showed that this cow raw milk sample comes under good quality and however all buffalo raw milk MBRT samples non-significantly retained maximum-minimum period (4.07±0.047 to 3.90±0.040 hrs) with under good quality milk (Table 1). The present result agreed with (Gupta et al 2020) reported that the average maximum-minimum period was 4.0 to 3.0 hours for the change its color from blue to white, which indicates that this milk sample comes under good quality. The significantly lower SPC of raw milk sample was recorded into sample no.…”
supporting
confidence: 93%
See 2 more Smart Citations